Diretrizes para implantação coletiva e semipresencial de sistemas certificáveis de gestão - Izeppe, Fábio Roberto [UNESP] (2013)
This paper aims to develop guidelines for the collective and semi-presence-based implementation of (a situation in which there is no active participation of a consultant specialist in the company) certifiable management systems. These systems include ISO 9001, ISO 14001, or OHSAS 18001. This is a theoretical and conceptual study which was based on four practical experiences of the theory of collective and semi-presence-based system implementation for the development of the guidelines proposed. These guidelines are drawn up according to the following items: selection of companies; awareness, diagnosis, planning, training, implementation, verification and improvement.